(untitled) (Eurasian Medical Research Periodical, 2022)
This study analyzed the method of surgical treatment of idopathic scoliosis in adolescents. All patients underwent surgery to correct idiopathic scoliosis using pedicle screws. 205 patients were operated on. All patients had good and satisfactory results